Spatial inequalities of COVID-19 mortality rate in relation to socioeconomic and environmental factors across England - Sun, Yeran; Hu, Xuke; Xie, Jing (The Science of the total environment, 2021)
In this study, we aimed to examine spatial inequalities of COVID-19 mortality rate in relation to spatial inequalities of socioeconomic and environmental factors across England. Specifically, we first explored spatial patterns of COVID-19 mortality rate in comparison to non-COVID-19 mortality rate. Subsequently, we established models to investigate contributions of socioeconomic and environmental factors to spatial variations of COVID-19 mortality rate across England (N = 317). Two newly developed specifications of spatial regression models were established successfully to estimate COVID-19 mortality rate (R2 = 0.49 and R2 = 0.793). The level of spatial inequalities of COVID-19 mortality is higher than that of non-COVID-19 mortality in England. Although global spatial association of COVID-19 mortality and non-COVID-19 mortality is positive, local spatial association of COVID-19 mortality and non-COVID-19 mortality is negative in some areas. Expectedly, hospital accessibility is negatively related to COVID-19 mortality rate. Percent of Asians, percent of Blacks, and unemployment rate are positively related to COVID-19 mortality rate. More importantly, relative humidity is negatively related to COVID-19 mortality rate. Moreover, among the spatial models estimated, the ‘random effects specification of eigenvector spatial filtering model’ outperforms the ‘matrix exponential spatial specification of spatial autoregressive model’. [Display omitted] •Investigating spatial variations of COVID-19 mortality rate across England•Hospital accessibility is negatively related to COVID-19 mortality rate.•Unemployment rate is positively related to COVID-19 mortality rate.•Relative humidity is negatively related to COVID-19 mortality rate.•The RES-ESF model outperforms the MESS-SAR model.